### Home > CCA > Chapter 10 > Lesson 10.3.3 > Problem 10-138

10-138.

If

*f*(*x*) =*x*^{2 }− 2 then:*f*(*x*) − 3 = (*x*^{2 }− 2) − 3also

*f*(2*x*) = (2*x*)^{2}− 2=

*x*^{2 }− 5= 4

*x*^{2 }− 2Use these same ideas with

*f*(*x*) = (*x*+ 1)^{2 }− 3 find these expressions:*10-138 HW eTool*(Desmos). Homework Help ✎*f*(*x*) + 3*f*(3*x*)3

*· f*(*x*)*f*(*x*+ 3)

This problem is similar to problem 10-118 from Lesson 10.3.1.

Use the same methods in that problem to help you with this one.

(*x* + 1)^{2}

3(*x* + 1)^{2} − 9

Use the eTool below to help you with this problem.

Click on the link at right for the full eTool version: CCA 10-138 HW eTool